Analyzing the Evolution of Transgender Protection: A Comparative Study of Transgender Protection Act of Pakistan 2018 and 2022 - Mazhar, Rumaiza (Annals of Human and Social Sciences, 2024)
This research paper focuses on the comprehensive examination of the transgender protection acts of Pakistan in 2018 and 2022. Transgender, a person with no specific gender is an important part of society. In society, they have been deprived of their basic rights. Related to this, the government of Pakistan passed a bill in 2018 to tackle the basic rights of Transgender community. Later, in 2022, an amendment bill has been presented to raise some questions regarding the 2018 bill. This study is based upon the qualitative approach to deal with this subject which includes the transgender protection bills, including the collection of data from secondary resources including media reports and other documents. It shows the implication of these acts on the rights and well-being of a transgender individual. Through a critical examination, this paper explores the policy intent and identifies the basic differences and similarities between the two acts related to transgender rights in Pakistan and how the issue mainly deals with the gender identity of a transgender person.